Non-dominant hand contractions do not facilitate performance under pressure in common desktop tasks - Yu Fan Eng; Daniel R. Little; Andy Yang; Anchalee Wensinger; Leo J. Roberts (PLoS ONE, 2025)
Non-dominant hand contractions (NDHCs) have been shown to help expert motor skills in high-pressure scenarios that induce performance anxiety. Most studies of NHDCs under pressure have examined benefits in overlearned specialist movements (e.g., sporting skills), while few have considered if NDHCs can aid common movements with population-wide expertise (e.g., typing). Accordingly, across three experiments, we explored if NDHCs could protect or facilitate performance under time and/or evaluation pressure in a cursor positioning task (Experiments 1 & 2) and a typing task (Experiment 3). Despite varying the nature of the task, pressure manipulation, and design, and successfully manipulating state anxiety in each experiment, we found no evidence that NDHCs assist performance under pressure in these tasks. For the pressure × contraction condition interaction, the largest inclusion Bayes Factor was .40 for task response time and .62 for task error (Experiment 1), indicating evidence in favour of a null result. Our results, along with other recent studies in this area, cast doubt on the benefits of NDHCs under pressure outside sporting tasks and underline the need for a better mechanistic account of the phenomenon.